Możliwości i ograniczenia wykorzystania krótkoterminowych papierów dłużnych w zarządzaniu płynnością finansową - Bartkiewicz, Agnieszka (Opportunities and Limitations of Using Commercial Papers in the Financial Liquidity Management, 2006)
Commercial papers market does not give possibilities of using all advantages of these instruments in the financial liquidity management. This situation is due to the fact that commercial papers market in Poland is still relatively immature and there are many obstacles to the development of this segment of financial market. The main problems which require solution are lack of unitary legal basis for this instruments and lack of transparency. Moreover, in reality a secondary market for trading commercial papers does not exist yet. The most investors keep commercial papers to maturity. It is important that so many barriers do not exclude possibility of using these papers in financial liquidity management, but elimination of these limitations could raise effectiveness of this management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 45-53